A Systematic Literature Review: Determinants of User Interest in Digital Payment Services: Trends and Causes - Indrijawati, Aini; Mediaty; Arham; Damayanti, Sri; Wahid, Muhammad Zulfadli (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to analyze the trends in digital payment usage, the key factors influencing adoption, and the roles of Perceived Usefulness and Perceived Ease of Use in driving user interest. A systematic literature review approach was employed, analyzing scholarly articles from the past decade (2014–2024), focusing on technological, behavioral, cultural, and regulatory aspects influencing digital payment adoption. The findings reveal that digital payment adoption has proliferated and is driven by technological advancements such as blockchain, regulatory support, and economic incentives. Perceived Usefulness emerges as a primary factor, offering benefits such as efficiency, cost savings, and enhanced financial inclusion. Meanwhile, Perceived Ease of Use, including intuitive interfaces and AI-based support, strengthens user engagement. This study highlights the importance of user-friendly and locally adaptive service designs. Practically, the findings provide strategic guidance for service providers and policymakers to prioritize intuitive designs, robust security frameworks, and digital literacy programs to foster the development of an inclusive and sustainable digital payment ecosystem.